2014
DOI: 10.1016/j.neurobiolaging.2014.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Exosome reduction in vivo is associated with lower amyloid plaque load in the 5XFAD mouse model of Alzheimer's disease

Abstract: We present evidence here that exosomes stimulate aggregation of Aβ1-42 in vitro and in vivo and interfere with uptake of Aβ by primary cultured astrocytes and microglia in vitro. Exosome secretion is prevented by inhibition of neutral sphingomyelinase 2 (nSMase2), a key regulatory enzyme generating ceramide from sphingomyelin, with GW4869. Using the 5XFAD mouse, we show that intraperitoneal injection of GW4869 reduces the levels of brain and serum exosomes, brain ceramide, and Aβ1-42 plaque load. Reduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
383
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 403 publications
(401 citation statements)
references
References 58 publications
(71 reference statements)
14
383
1
3
Order By: Relevance
“…Indeed, they found that systemically administration of GW4869 could reduce the total exosomes in serum and treat allergic, cardiac and Alzheimer's dysfunction 29, 30, 31. Thus, our findings provide a potential method to prevent endothelial inflammation and atherosclerosis.…”
Section: Discussionmentioning
confidence: 63%
“…Indeed, they found that systemically administration of GW4869 could reduce the total exosomes in serum and treat allergic, cardiac and Alzheimer's dysfunction 29, 30, 31. Thus, our findings provide a potential method to prevent endothelial inflammation and atherosclerosis.…”
Section: Discussionmentioning
confidence: 63%
“…Exosomes were found to stimulate the aggregation of A␤ by isolating exosomes from brain tissue of the 5ϫFAD mouse model of AD (79). Inhibition of exosome formation in this model using GW4869, an inhibitor of neutral sphingomyelinase, resulted in the reduction of amyloid plaques in the brain.…”
Section: Exosomes and The Transmission Of Ad Pathologymentioning
confidence: 99%
“…At present there is some controversy in the field as to the role of EVs in AD; while some studies (59)(60)(61) suggest that exosome-associated Aβ is protective, other studies suggest that exosome-associated Aβ contributes neurotoxic amyloid formation (56,(62)(63)(64)(65). Moreover, misfolded tau protein, which is implicated in Aβ aggregate formation, may also be released from neurons via EVs (66).…”
Section: Evs In Physiology and Pathology Of The Nervous Systemmentioning
confidence: 99%